(untitled) (Sains Humanika, 2020)
This study aims to examine the direct effect of safety climate and the mediation effect of safety knowledge on laboratory safety behavior among university students. The quantitative method using questionnaires was used in this study. A total of 278 chemical engineering students at three public universities were involved in this study. Data were analyzed using descriptive and inferential statistics via IBM SPSS Statistics and SEM SmartPLS 3.0. From the study, management commitment, supervisor commitment, student commitment, risk perception, and safety reward were able to shape the safety climate construct. Meanwhile, safety compliance and safety participation were able to develop the laboratory safety behavior construct. This study confirmed that safety climate had a direct effect on laboratory safety behavior. Besides, safety knowledge has mediated the relationship between safety climate and laboratory safety behavior among university students. In this study, the mediation effect of safety knowledge provided a superior result compared to the direct impact. Safety knowledge was an essential element in the management of laboratory safety. The management of the universities, therefore, should recognize the importance of offering subjects related to occupational safety to the program which operates laboratory facilities. For a reason, this study has confirmed that safety subjects could enhance safety knowledge and have a positive impact on laboratory safety behavior among students. Hence, the study of the relationship between safety climate and laboratory safety behavior should be discovered in other educational organizations such as private universities, teacherâ€™s education institutes (IPG), polytechnics, and community colleges.Â